TECHNOLOGY FOR IMPROVING THE DURABILITY OF CONCRETE IN THE DRY HOT CLIMATE OF UZBEKISTAN - Karakulov , Kholmeli; Nasirov, Navruz (Science technology&Digital finance, 2023)
Annotation. The article is devoted to the method of manufacturing concrete in the conditions of the dry hot climate of Uzbekistan, methods and tools of construction technology are used in the study of this problem. The article analyzes the characteristic features of construction technology, taking into account the influence of different local resources. Based on the results of the study, relevant recommendations and proposals have been prepared for the decision-maker (LPR)